2021
DOI: 10.33102/sainsinsani.vol6no3.344
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Systematic Literature Review (SLR) Tentang Kesihatan Mental Di Malaysia Semasa Pandemik Covid-19

Abstract: Kesihatan mental boleh mempengaruhi kesihatan fizikal, kualiti hidup dan produktiviti seseorang. Namun begitu, peningkatan isu kesihatan mental dalam kalangan masyarakat di Malaysia pada hari ini berada pada tahap yang membimbangkan. Tambahan pula, penyebaran wabak pandemik Covid-19 pada tahun 2019 telah mengubah kehidupan normal manusia sekaligus berpotensi menjadi faktor yang mempengaruhi kesihatan mental terutamanya dalam kalangan masyarakat di negara ini. Kajian ini bertujuan untuk melihat tema kajian dan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on 22 articles, the study identified three crucial gaps in the study of developing emotional intelligence using storybooks as a learning tool: 1) There is a dearth of research on the relationship between storybooks and emotional intelligence in preschoolers; 2) There is a need for more research in Malaysia on the effects of storybooks on preschoolers' emotional intelligence, and 3) Limited research on children's storybooks and emotional intelligence. Table 2, adapted from previous research (Rahman et al, 2021), indicates how three gaps in the study of developing emotional intelligence using story books as a learning tool were identified: x 11 Buono (2017) x 12 Ozdemir (2017) x 13 Boris (2017) x 14 Shanty (2016) x…”
Section: Discussionmentioning
confidence: 99%
“…Based on 22 articles, the study identified three crucial gaps in the study of developing emotional intelligence using storybooks as a learning tool: 1) There is a dearth of research on the relationship between storybooks and emotional intelligence in preschoolers; 2) There is a need for more research in Malaysia on the effects of storybooks on preschoolers' emotional intelligence, and 3) Limited research on children's storybooks and emotional intelligence. Table 2, adapted from previous research (Rahman et al, 2021), indicates how three gaps in the study of developing emotional intelligence using story books as a learning tool were identified: x 11 Buono (2017) x 12 Ozdemir (2017) x 13 Boris (2017) x 14 Shanty (2016) x…”
Section: Discussionmentioning
confidence: 99%
“…These stresses indirectly affect the level of health and well-being of the individual. According to Kamal et al (2021) mental health is the ability of an individual, a group to interact with each other in an environment as well as achieve optimal overall well-being or can be defined as the cognitive ability and effective connection of an individual or group towards a set goal. In addition, the level of mental health can affect the way a person thinks, behaves and emotions to solve problems, determine choices in life or make decisions and interact well with others.…”
Section: Introductionmentioning
confidence: 99%